MODERATION PERCEIVED SOCIAL RELATEDNESS IN THE INFLUENCE OF BRAND TRUST ON SOCIAL MEDIA BRAND ENGAGEMENT - Cen Lu; Chandra Kuswoyo; Felicia Abednego; Markus Kendrick (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the effect of brand trust on social media brand engagement (SMBE) with perceived social relatedness as a moderating variable. In today's digital era, social media has become an important platform for brands to build relationships with consumers, especially Generation Y who are very active on social media. This study uses a quantitative approach with a survey method on social media users in the Bandung area. The results of the study indicate that brand trust has a significant effect on SMBE. In addition, perceived social relatedness is proven to moderate the relationship positively and significantly. This means that the level of social relatedness felt by consumers can strengthen the influence of trust in brands in increasing consumer engagement on social media. These findings provide important implications for marketing practitioners to not only build trust in brands but also create a sense of social relatedness among consumer communities in their social media strategies.